2023
DOI: 10.1021/acs.jafc.3c04150
|View full text |Cite
|
Sign up to set email alerts
|

Broccoli-Derived Exosome-like Nanoparticles Alleviate Loperamide-Induced Constipation, in Correlation with Regulation on Gut Microbiota and Tryptophan Metabolism

Tianchi Duan,
Xiaoyuan Wang,
Xinyue Dong
et al.

Abstract: Constipation, a common gastrointestinal dysfunction, damages patients' life quality and predisposes them to other serious diseases. Current strategies against constipation often cause drug dependency and side effects. Here, we demonstrated that broccoli-derived exosome-like nanoparticles (BENs), a natural product with high gastrointestinal stability, ameliorated LOP-induced constipation in mice. Specifically, orally administered BENs (17.5 mg/kg/d) effectively shortened defecation time, sped up intestinal prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Additionally, the metabolism of bile acids (BAs) is essential for managing constipation-related symptoms. Bacteroidetes influence this process by stimulating colonic motility through alterations in the bile acid pool composition ( Duan et al, 2023 ). Our study indicates that a high abundance of Bacteroidetes is a risk factor for constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the metabolism of bile acids (BAs) is essential for managing constipation-related symptoms. Bacteroidetes influence this process by stimulating colonic motility through alterations in the bile acid pool composition ( Duan et al, 2023 ). Our study indicates that a high abundance of Bacteroidetes is a risk factor for constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this approach seeks to minimize potential adverse reactions associated with the metabolic energy effects of AMPK. In another study, BDEVs were shown to alleviate LOP-induced constipation in mice by influencing gastrointestinal hormones, gut microbial structure, and intestinal metabolites [78]. These research findings underscore the promising potential of developing BDEVs as safe and effective nano-therapies for the treatment of constipation [78].…”
Section: Broccoli Derived Extracellular Vesicles (Bdevs)mentioning
confidence: 97%
“…Generally, they are extracted from edible plants, can be efficiently produced in large quantities, and can compensate for the limitations of mammal-derived exosomes, which have attracted more and more attention (Cao et al 2023 ). At present, there are exosomes from grape (Teng et al 2022 ), broccoli (Duan et al 2023 ), ginger (Zhu and He 2023 ), carrot (Mu et al 2014 ), and other sources (Record 2013 ), which are similar to general animal derived exosomes in terms of size distribution, morphology, and contents. They also have certain clinical applications.…”
Section: Exosomementioning
confidence: 99%